Standar Operasional Prosedur (SOP) Pelayanan Publik di Kantor Desa Tellulimpoe Kecematan Majauleng Kabupaten Wajo - Musfira Indrayana; Jamal Qadar; Syamsiar Syamsiar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Standard Operating Procedures (SOP) are documents that contain a series of standardized written instructions regarding various office administration processes. This document includes how to carry out the work, the time of implementation, the place of implementation, and the actors involved in the activity. SOP is one of the main references regarding steps or stages related to applicable activities which are work activities in an agency, therefore SOP can be said to be a series of written instructions carried out regarding various government administration processes. This research aims to reveal the SOP at the Telullimpoe Village Office in providing services for making indigent certificates, especially in Tellulimpoe Village, Majauleng District, Wajo Regency. For this reason, information collection is carried out through direct observation, filling out questionnaires, and collecting supporting data in the form of official documents. The results of the research show that the SOP for the service of making disability certificates in Tellulimpoe Village, Majauleng District, Wajo Regency is very good. This is supported by research results which reveal that the SOP in the service for making certificates cannot be included in the very good category.